Arthroscopic repair of ulnar-sided triangular fibrocartilage complex (Palmer type 1B) tears: a comparison between short- and midterm results - Wolf, Maya Barbara; Haas, Andreas; Hahn, Peter; Unglaub, Frank (The journal of hand surgery. [American volume], 2012)
Purpose To compare short- and midterm functional and subjective outcomes of arthroscopically repaired Palmer 1B tears. Methods At 2 time points, we evaluated 49 patients with Palmer 1B tears who underwent arthroscopic repair. We examined 46 patients (23 males and 23 females) in the short-term at an average of 11 months (range, 6-23 mo) postoperatively. In a second midterm follow-up, we examined 40 patients (20 males and 20 females) an average of 4.8 years (range, 4.2-5.9 y) after repair. Between short- and midterm follow-ups, 6 patients underwent an ulnar-shortening osteotomy to alleviate persistent ulnar-sided symptoms. Objective and subjective evaluation included the determination of range of motion, grip strength, pain, and wrist scores (modified Mayo wrist score and Disabilities of Arm, Shoulder, and Hand score). Results Compared with short-term repair results, midterm outcomes showed a further improvement in pain, wrist scores, grip strength, and motion. Neither static nor dynamic ulnar variance was correlated to preoperative and postoperative Disabilities of the Arm, Shoulder, and Hand scores, short-term modified Mayo wrist scores, or need for ulnar-shortening osteotomy. Five patients improved only after having received an ulnar shortening osteotomy. Conclusions After repair of Palmer 1B lesions, patients continued to improve in function and comfort at least into the second year, although some needed to have the ulna shortened to achieve this result. Type of study/level of evidence Therapeutic IV.
Gesehen am 08.10.2018